Tolosa Igualada, Miguel; De Faria Pires, Loïc. Manual de traducció català-francès - Daniel Gallego Hernández (Quaderns)
Tolosa Igualada, Miguel; De Faria Pires, Loïc Manual de traducció català-francès Vic: Eumo, 2022, 208 p. ISBN 978-84-9766-789-0